ChemInform Abstract: Novel and Convenient Synthesis of Benzofurans from Dihydrocoumarins. Issue 4 (31st January 2013) - Shachan‐Tov, Sharona; Frimer, Aryeh A.
Abstract Benzofurans (VII) are unexpectedly synthesized from coumarins (III) through esters (V).